Detergent and water recovery from laundry wastewater using tilted panel membrane filtration system - Barambu, N.U. (MDPI AG, 2020)
Increasing global concern on clean water scarcity and environmental sustainability drive invention in water reclamation technology. Laundry wastewater reclamation via membrane technology faces the challenge of membrane fouling. This paper assesses a tilting-the-filtration-panel filtration system for the treatment of real laundry wastewater filtration aimed for water and detergent reuse. Results showed that the panel tilting significantly improved fouling control and enhanced permeability due to enhanced contact of air bubbles with the membrane surface, which induced continuous detachment of foulant from the membrane surface. The combination of aeration rate and tilting angle resulted in up to 83 permeability enhancement from 109 to 221.4 ± 10.8 (L/m2·h·bar). The system also offers 32 detergent recovery. Overall findings suggest that the system offers an attractive approach for both fouling management and detergent recovery and can potentially be applied under a simple setup in which filtration can be driven by gravity/hydrostatic pressure. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.